DEONTOLOGI PEMERINTAHAN DAERAH DI INDONESIA (Oase Akuntabilitas Politik dalam Perspektif Partisipasi Politik) - IRWAN NOOR, IRWAN NOOR (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractAccountability is often believed to be the embodiment of democratic society, so oftenrelied upon by local government. However, by criticizing the Law 32/2004, the need to furtherunderstanding of the concept, particularly with the Development state Theory and RationalChoice Model in Political TheoryKeyword: Accountability, Political Participation